2011
DOI: 10.1111/j.1471-4159.2011.07308.x
|View full text |Cite
|
Sign up to set email alerts
|

Casein kinase 1 enables nucleus accumbens amphetamine‐induced locomotion by regulating AMPA receptor phosphorylation

Abstract: The closely related δ and ε isoforms of the serine/threonine protein kinase casein kinase 1 (Csnk1) have been implicated in the generation of psychostimulant-induced behaviors. Here we show that Csnk1δ/ε produces its effects on behavior by acting on the Darpp-32-PP1 signaling pathway to regulate AMPA receptor phosphorylation in the nucleus accumbens (NAcc). Inhibiting Csnk1δ/ε in the NAcc with the selective inhibitor PF-670462 blocks amphetamine induced locomotion and its ability to increase phosphorylation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 49 publications
(126 reference statements)
1
27
2
Order By: Relevance
“…In contrast to the results observed with PF-4800567, we previously found that the CK-1 inhibitor PF-670462 decreased MA sensitivity (Bryant et al, 2009b;Li et al, 2011). PF-670462 was previously thought to be slightly more selective for Csnk1e over Csnk1d (Badura et al, 2007), but a recent study showed that PF-670462 was six-fold more selective for Csnk1d over Csnk1e and that PF-4800567 was 20-fold more selective for Csnk1e over Csnk1d (Walton et al, 2009).…”
Section: Discussioncontrasting
confidence: 78%
See 3 more Smart Citations
“…In contrast to the results observed with PF-4800567, we previously found that the CK-1 inhibitor PF-670462 decreased MA sensitivity (Bryant et al, 2009b;Li et al, 2011). PF-670462 was previously thought to be slightly more selective for Csnk1e over Csnk1d (Badura et al, 2007), but a recent study showed that PF-670462 was six-fold more selective for Csnk1d over Csnk1e and that PF-4800567 was 20-fold more selective for Csnk1e over Csnk1d (Walton et al, 2009).…”
Section: Discussioncontrasting
confidence: 78%
“…Together, these results suggest that both Csnk1e and Csnk1d are important for sensitivity to drugs of abuse. However, because PF-670462 only exhibits six-fold selectivity for Csnk1d over Csnk1e (Walton et al, 2009;Meng et al, 2010), it is unclear if our previous results were mediated by Csnk1d or Csnk1e (Bryant et al, 2009b;Li et al, 2011).…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…This mechanism is vital for centrosome translocation to the IS (Zyss et al, 2011). CK1δ was also shown to be involved in psychostimulant-induced behaviours by acting on the Darpp-32-PP1 signalling pathway to regulate AMPA receptor phosphorylation in the nucleus accumbens (Li et al, 2011).…”
Section: Introductionmentioning
confidence: 99%